Leishmania infantum Infection Modulates the Jak-STAT Pathway in Lutzomyia longipalpis LL5 Embryonic Cells and Adult Females, and Affects Parasite Growth in the Sand Fly - Telleria, Erich Loza; Azevedo-Brito, Daisy Aline; Kykalová, Barbora; Tinoco-Nunes, Bruno; Pitaluga, André Nóbrega; Volf, Petr; Traub-Csekö, Yara Maria (Frontiers in Tropical Diseases, 2021)
Phlebotomine sand flies (Diptera, Psychodidae) belonging to the Lutzomyia genus transmit zoonoses in the New World. Lutzomyia longipalpis is the main vector of Leishmania infantum, which is the causative agent of visceral leishmaniasis in Brazil. To identify key molecular aspects involved in the interaction between vector and pathogens and contribute to developing disease transmission controls, we investigated the sand fly innate immunity mediated by the Janus kinase/signal transducer and activator of transcription (Jak-STAT) pathway in response to L. infantum infection. We used two study models: L. longipalpis LL5 embryonic cells co-cultured with L. infantum and sand fly females artificially infected with the parasite. We used qPCR to follow the L. longipalpis gene expression of molecules involved in the Jak-STAT pathway. Also, we modulated the Jak-STAT mediated immune response to understand its role in Leishmania parasite infection. For that, we used RNAi to silence the pathway regulators, protein inhibitor of activated STATs (PIAS) in LL5 cells, and STAT in adult females. In addition, the pathway suppression effect on parasite development within the vector was assessed by light microscopy in late-phase infection. The silencing of the repressor PIAS in LL5 cells led to a moderate increase in a protein tyrosine phosphatase 61F (PTP61F) expression. It suggests a compensatory regulation between these two repressors. L. infantum co-culture with LL5 cells upregulated repressors PIAS, suppressor of cytokine signaling (SOCS), and PTP61F. It also downmodulated virus-induced RNA-1 (VIR-1), a pathway effector, indicating that the parasite could repress the Jak-STAT pathway in LL5 cells. In Leishmania-infected L. longipalpis females, STAT and the antimicrobial peptide attacin were downregulated on the third day post-infection, suggesting a correlation that favors the parasite survival at the end of blood digestion in the sand fly. The antibiotic treatment of infected females showed that the reduction of gut bacteria had little effect on the Jak-STAT pathway regulation. STAT gene silencing mediated by RNAi reduced the expression of inducible nitric oxide synthase (iNOS) and favored Leishmania growth in sand flies on the first day post-infection. These results indicate that STAT participated in the iNOS regulation with subsequent effect on parasite survival.